Clinical features and risk factors of flare in anti-synthetase syndrome - Hasegawa, Anna; Kurasawa, Kazuhiro; Koike, Ryota; Sato, Rika; Kikuchi, Azusa; Komatsu, Sara; Sakaue, Yusuke; Aizawa, Yuki; Shimizu, Aya; Yoshida, Yuhi; Hiyama, Tomoka; Miyao, Tomoyuki; et al. (Clinical rheumatology, 2025)
Objectives To clarify clinical features and risk factors of flares in anti-synthetase syndrome (ASS). Methods We retrospectively identified consecutive patients with ASS by reviewing medical records. Clinical, laboratory, and imaging data were obtained. Patients were considered to have a flare when treatment was intensified for myositis and/or ILD with an increased dose of glucocorticoid (GC) and/or addition of a new immunosuppressant (IS). Results A total of 51 subjects were included. All 51 patients had ILD, 38 patients had myositis, and 39 patients had skin rash. Anti-aminoacyl-tRNA synthetase (ARS) antibody subtypes were anti-Jo-1 in 23 (45%), anti-EJ in 13 (25%), anti-PL-7 in 8 (16%), and anti-PL-12 in 7 (14%). As initial therapy, half of the patients were treated with GCs alone, while the rest were treated with a combination of GCs and ISs during observation. Flares occurred in 30 (58%) mostly when the prednisolone dose was tapered to 11 mg/day. Patients with anti-EJ or anti-Jo-1 frequently flared. The use of calcineurin inhibitors (CNIs) was significantly associated with less flares of myositis but not with those of ILD. In multivariate analyses, anti-ARS subtype and Gottron’s sign were identified as independent risk factors for overall flare. Conclusion The majority of ASS patients experienced a flare, which frequently occurred when the GC dose was tapered to 11 mg of prednisolone. The presence of anti-EJ/Jo-1 antibody and Gottron’s sign were identified as independent risk factors for flare. In addition, the use of CNIs tended to associate with less flares of myositis. Key Points • The majority of patients with anti-synthetase syndrome experience a flare when glucocorticoids are tapered close to 10 mg of prednisolone . • The presence of anti-EJ/Jo-1 antibody and Gottron’s sign are risk factors for flares in patients with anti-synthetase syndrome . • The use of calcineurin inhibitors may prevent flares of myositis in patients with anti-synthetase syndrome .